PERAN PENDIDIKAN TINGGI DALAM MENGEMBANGKAN SENI GRAFIS DI INDONESIA - Damayanti, Nuning Y (Jurnal Budaya Nusantara, 2019)
Conventional Graphic Art is understood by academics through the history of its development.The Chinese nation is thought to have started the tradition of print as the forerunner of graphicart in its 'primitive' era, while the Romans began etching-glass techniques for portraying gladiators.Furthermore, the Japanese in the 8th century had begun their first authentic print by tracing andprinting Buddhist faces. When the Europeans used it as a printing technique as a medium forartistic expression, the word "printmaking" emerged, which was later adopted by the field of artuntil now. Later the graphic arts were increasingly used to reproduce various human needs. Inearly 1900 the Dutch introduced the technique of Graphic Printing in education at the BandungTechnical College is now the Bandung Institute of Technology. History and development ofIndonesian Graphic Arts in history began at Institute of Technology Bandung (ITB) as the firstacademic provider of formal education in the Department of Fine Arts, then now a Faculty ofFine Arts and Design (FSRD) of ITB. Conventional Graphic Printing Techniques become oneof the main areas of interest, the Graphic Arts Studio of the Fine Arts Department, then becamethe Fine Art Study Program and the Graphic Art Printing Technique until now is still the mainarea of interest and subject matter in the curriculum of the FSRD ITB Fine Arts Study Program.